KAPASITAS PENGELOLA ELEKTRONIK WARUNG GOTONG ROYONG (E-WARONG) KELOMPOK USAHA BERSAMA (KUBE) JASA SAHABAT KITA DI KECAMATAN TAMPAN KOTA PEKANBARU - Wahyu Desta Beni; Abdul Sadad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Poverty is still a big problem in people's lives and makes individuals unable to produce anything, causing unwanted behavior and looking for wrong ways to fulfill their daily needs such as begging, stealing and so on. The electronic mutual coorporation stall joint bussiness group at program of family expectations program is the flagship program of the Indonesian Ministry of Social Affairs in the context of poverty alleviation. electronic mutual coorporation stall joint bussiness group is an agency managed by the joint bussiness group service in the framework of serving non-cash disbursement of food aid, carrying out productive economic businesses as well as a means of sustainable business to improve the welfare or economy of the manager. Therefore, the management capacity of the electronic mutual coorporation stall joint bussiness group service is needed so that the benefits of this program are felt by managers and recipients of non-cash social assistance. The purpose of this study is to determine how the capacity of the management of the electronic mutual coorporation stall joint bussiness group service Sahabat Kita in Tampan District and to know the factors that affect the capacity of manager the electronic mutual coorporation stall joint bussiness group Sahabat Kita. This research uses qualitative research and the determination of informants using purposive sampling technique and primary and secondary data obtained through observation, interviews and documentation and then analyzed based on the research problem. The result of this study indicate that managers electronic stalls mutual aid business group Sahabat Kita have not shown a high capacity in managing electronic stalls mutual aid business group. The large number of inactive members made several electronic stalls mutual aid business group activities not carried out, such as the marketing of products and the target beneficiary families taht had to be served had not been achieved. And there is no cooperation with the external parties. As a result, almost 3 years of operation, member of electronic mutual coorporation stall joint bussiness group service Sahabat Kita not have graduated independently. Keyword: Management Capacity, electronic mutual coorporation stall joint bussiness group service Sahabat Kita